Review of the oar-head leafhopper genus Nacolus Jacobi (Hemiptera: Cicadellidae: Hylicinae) - Tang, Jiu; Zhang, Yalin (Zootaxa, 2019)
Six species in genus Nacolus Jacobi 1914 and one species in genus Melliola Hedicke 1923 are found to be synonyms. The following new synonyms are proposed for Nacolus tuberculatus (Walker 1858): Nacolus gavialis Jacobi 1914 syn. n.; Nacolus assamensis (Distant 1918) syn. n.; Nacolus sinensis (Ouchi 1938) syn. n.; Nacolus fuscovittatus Kuoh 1992 syn. n.; Nacolus nigrovittatus Kuoh 1992 syn. n. and Melliola granulata Schmidt 1920 syn. n. The genus Nacolus is reviewed with re-descriptions and photographs of external morphology and genitalia of males and females.